A Survey on Knowledge representation learning - Pallavi S. Deshpande (AG Volumes, 2022)
Knowledge representation is among AI’s most basic questions as well as one of its most essential notions. Extension data mining, on the other hand, generates transformable information, that expands knowledge base required for the generation of an extension strategy. Utilizing finite automata, we now have a novel way to describe knowledge in the context of the data mining. This paper offer a brief review of the structure and techniques that have been developed in this different discipline.